Screening for latent tuberculosis infection by an Aboriginal Community Controlled Health Service, New South Wales, Australia, 2015 - Hannah Visser (Western Pacific Surveillance and Response, 2020)
Objective: Ongoing transmission of tuberculosis (TB) continues in Indigenous communities in New South Wales (NSW), Australia. In a pilot project, a Public Health Unit TB team partnered with an Aboriginal Community Controlled Health Service (ACCHS) in a community with a cluster of TB to augment screening for latent TB infection (LTBI) using interferon-gamma release assay (IGRA). This study examined screening data and programme outcomes at 12 months post hoc to advise practice and policy formulation.